Pulmonary myxoid liposarcoma in a Holstein cow: Case report - Córdoba Parra, Juan David (2021)
A 14-year-old Holstein cow was referred to the Large Animal Clinic of the University of La Salle, Bogotá, Colombia, from a dairy farm in Sopo, Cundinamarca, with a history of anorexia, a very marked respiratory condition and physical exhaustion associated with dyspnea. The clinical examination shows fever (39.9 ºC), tachycardia (103 beats per minute), tachypnea (50 breaths per minute), mixed dyspnea with abdominal breathing, rales and wheezing along the pulmonary border, presence of large areas of pulmonary consolidation and mucopurulent bilateral nasal discharge, giving a presumptive diagnosis a severe mucopurulent pneumonia. By request of the owner, the patient is euthanized and necropsied, finding a large part of the lung lobes with a puffy texture, multiple “yellowish-green” masses of various sizes and diffusely in all the lung lobes. The histopathology results reported a pulmonary myxoid liposarcoma as a definitive diagnosis.